Perinephric myxoid pseudotumor of fat: the first case report in China with an updated literature review - Yang, Yu-Hang; Zhang, Yue-Ming; Liu, An-Hao; Luo, Guang-Cheng; Liu, Zheng-Jin; Xie, Jian-Wei (Frontiers in Oncology, 2025)
The perinephric myxoid pseudotumor of fat (PMPF) is an uncommon benign neoplasm characterized by a favorable prognosis. To date, 21 cases of PMPFs have been reported worldwide, and their detailed characteristics have not been fully elucidated. We report the 22nd case of PMPF, which is the first case in China and happened in a 54-year-old male with a 5.6 cm mass located in the lower inner aspect of the right kidney. The patient underwent a minimally invasive robot-assisted laparoscopic resection of the renal mass. Postoperative histopathological, immunohistochemical, and genetic testing results confirmed the diagnosis of PMPF. No evidence of recurrence was found during a follow-up period of 6 months postoperatively based on clinical and imaging data. This is a report of an unusual case of PMPF with an up-to-date review. According to the latest systematic review and clinical confirmation, PMPF is strongly associated with chronic kidney disease, which is further confirmed by our case. For PMPF, combining imaging methods and immunohistochemical staining is suggested, which may prove beneficial in clinical practice.